Sediments From a Seasonally Euxinic Coastal Ecosystem Show High Nitrogen Cycling Potential - Isabel M. L. Rigutto; Ştefania C. Sburlan; Lars W. P. de Bont; Tom Berben; Rob M. de Graaf; Caroline P. Slomp; Mike S. M. Jetten (Environmental Microbiology, 2025)
Coastal ecosystems are susceptible to eutrophication and deoxygenation, which may alter their nitrogen cycle dynamics. Here, we investigated the microbial nitrogen cycling potential in the sediment of a seasonally euxinic coastal ecosystem (Lake Grevelingen, NL) in winter and summer. Activity tests revealed ammonium (NH 4 + ) oxidation potential with maximum potential rates up to 53 μmol g −1 day −1 , even in anoxic sediment layers. A nitrifying microbial community was present in both oxic and anoxic sediment sections (up to 1.4% relative abundance). Nitrate (NO 3 − ), nitrite (NO 2 − ), and nitrous oxide (N 2 O) reduction potential were prominent across all sediment sections, with the highest potential rates (167 μmol NO 3 −∙ g −1 day −1 ) in the surface sediment in summer. Denitrification (79.3%–98.4%) and dissimilatory nitrate reduction to ammonium (DNRA; 1.6%–20.7%) were the major NO 3 − removal pathways, as supported by the detection of the narG/napA , nirK/nirS , norB , nosZ and nrfA/otr genes in all sediment sections. The DNRA contribution increased with depth and with the addition of electron donors, such as monomethylamine. Anaerobic ammonium oxidation (anammox) was not detected in these eutrophic sediments. Combined, our results show that there is high potential for nitrogen removal in eutrophic coastal ecosystems, which may help further restoration measures.

Recovery from multi‐millennial natural coastal hypoxia in the Stockholm Archipelago, Baltic Sea, terminated by modern human activity - Niels A. G. M. van Helmond; Bryan C. Lougheed; Annika Vollebregt; Francien Peterse; Guillaume Fontorbe; Daniel J. Conley; Caroline P. Slomp (Limnology and Oceanography, 2020)
Enhanced nutrient input and warming have led to the development of low oxygen (hypoxia) in coastal waters globally. For many coastal areas, insight into redox conditions prior to human impact is lacking. Here, we reconstructed bottom water redox conditions and sea surface temperatures (SSTs) for the coastal Stockholm Archipelago over the past 3000 yr. Elevated sedimentary concentrations of molybdenum indicate (seasonal) hypoxia between 1000 b.c.e. and 1500 c.e . Biomarker‐based (TEX 86 ) SST reconstructions indicate that the recovery from hypoxia after 1500 c.e. coincided with a period of significant cooling (∼ 2°C), while human activity in the study area, deduced from trends in sedimentary lead and existing paleobotanical and archeological records, had significantly increased. A strong increase in sedimentary lead and zinc, related to more intense human activity in the 18 th and 19 th century, and the onset of modern warming precede the return of hypoxia in the Stockholm Archipelago. We conclude that climatic cooling played an important role in the recovery from natural hypoxia after 1500 c.e. , but that eutrophication and warming, related to modern human activity, led to the return of hypoxia in the 20 th century. Our findings imply that ongoing global warming may exacerbate hypoxia in the coastal zone of the Baltic Sea.

Hypoxia in the Baltic Sea: Biogeochemical Cycles, Benthic Fauna, and Management - Jacob Carstensen; Daniel J. Conley; Erik Bonsdorff; Bo G. Gustafsson; Susanna Hietanen; Urzsula Janas; Tom Jilbert; Alexey Maximov; Alf Norkko; Joanna Norkko; Daniel C. Reed; Caroline P. Slomp; et al. (Ambio, 2014)

Does microbial stoichiometry modulate eutrophication of aquatic ecosystems? - A. K. Steenbergh; P. L. E. Bodelier; M. Heldal; C. P. Slomp; H. J. Laanbroek (Environmental Microbiology, 2013)
Summary The stoichiometry of prokaryotes ( B acteria and A rchaea ) can control benthic phosphorus ( P ) fluxes relative to carbon ( C ) and nitrogen ( N ) during organic matter remineralization. This paper presents the first experimental data on benthic microbial stoichiometry. We used X ‐ray microanalysis to determine C : N : P ratios of individual prokaryotes from C ‐limited B altic S ea sediments incubated under oxic or anoxic conditions. At approximately 400:1, C : P ratios of prokaryotes from both oxic and anoxic incubations were higher than the R edfield ratio for marine organic matter (106:1), whereas prokaryotic C : N ratios (6.4:1) were close to the R edfield ratio. We conclude that high microbial C : P ratios contribute to the enhanced remineralization of P from organic matter relative to C and N observed in many low oxygen marine settings.

A welcome can of worms? Hypoxia mitigation by an invasive species - Joanna Norkko; Daniel C. Reed; Karen Timmermann; Alf Norkko; Bo G. Gustafsson; Erik Bonsdorff; Caroline P. Slomp; Jacob Carstensen; Daniel J. Conley (Global Change Biology, 2012)
Invasive species and bottom‐water hypoxia both constitute major global threats to the diversity and integrity of marine ecosystems. These stressors may interact with unexpected consequences, as invasive species that require an initial environmental disturbance to become established can subsequently become important drivers of ecological change. There is recent evidence that improved bottom‐water oxygen conditions in coastal areas of the northern Baltic Sea coincide with increased abundances of the invasive polychaetes M arenzelleria spp. Using a reactive‐transport model, we demonstrate that the long‐term bioirrigation activities of dense M arenzelleria populations have a major impact on sedimentary phosphorus dynamics. This may facilitate the switch from a seasonally hypoxic system back to a normoxic system by reducing the potential for sediment‐induced eutrophication in the upper water column. In contrast to short‐term laboratory experiments, our simulations, which cover a 10‐year period, show that M arenzelleria has the potential to enhance long‐term phosphorus retention in muddy sediments. Over time bioirrigation leads to a substantial increase in the iron‐bound phosphorus content of sediments while reducing the concentration of labile organic carbon. As surface sediments are maintained oxic, iron oxyhydroxides are able to persist and age into more refractory forms. The model illustrates mechanisms through which M arenzelleria can act as a driver of ecological change, although hypoxic disturbance or natural population declines in native species may be needed for them to initially become established. Invasive species are generally considered to have a negative impact; however, we show here that one of the main recent invaders in the Baltic Sea may provide important ecosystem services. This may be of particular importance in low‐diversity systems, where disturbances may dramatically alter ecosystem services due to low functional redundancy. Thus, an environmental problem in one region may be either exacerbated or alleviated by a single species from another region, with potentially ecosystem‐wide consequences.

Sedimentary phosphorus dynamics and the evolution of bottom‐water hypoxia: A coupled benthic–pelagic model of a coastal system - Daniel C. Reed; Caroline P. Slomp; Bo G. Gustafsson (Limnology and Oceanography, 2011)
The present study examines oxygen and phosphorus dynamics at a seasonally hypoxic site in the Arkona basin of the Baltic Sea. A coupled benthic–pelagic reactive‐transport model is used to describe the evolution of bottom‐water solute concentrations, as well as pore‐water and sediment profiles. Aerobic respiration dominates remineralization, with iron reduction, denitrification, and sulphate reduction playing secondary roles, while other pathways are negligible. Sediments represent a significant oxygen sink chiefly due to the aerobic degradation of organic matter, as well as nitrification and iron oxyhydroxide precipitation. Most phosphorus deposited in sediments is in organic matter, yet cycling is dominated by iron‐bound phosphorus due to rapid dissimilatory iron reduction coupled with aerobic iron oxyhydroxide formation. Sustained hypoxia results in an initial decrease in sediment phosphorus content due to dissolution of phosphorus‐bearing iron oxyhydroxides, resulting in a pulse of phosphate to overlying waters. Although an organic‐rich layer is formed under low‐oxygen conditions, enhanced remineralization of organic phosphorus relative to organic carbon tempers sedimentary phosphorus accumulation. Upon reoxygenation of bottom waters after a decade of sustained hypoxia, oxygen concentrations do not immediately achieve values observed prior to hypoxia because the organic‐rich layer creates a higher benthic oxygen demand. Artificial reoxygenation of bottom waters leads to a substantial increase in the iron‐bound phosphorus pool; the total phosphorus content of the sediment, however, is unaffected. A relapse into hypoxia would consequently produce a large pulse of phosphate to the overlying waters potentially exacerbating the situation.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)